Perkembangan Pendidikan Islam Masa Awal di Sulawesi - Ismail (Medan Resource Center, 2022)
This article aims to discuss the development of early Islamic education in Sulawesi. The arrival of Islam in Sulawesi was a bit late when compared to other regions in Indonesia, such as Sumatra, Java, Kalimantan and Maluku. This is due to the fact that the kingdom of Gowa was known as an influential kingdom and became a kingdom in the early 17th century. There were three figures who played an important role in the process of Islamization of Sulawesi, namely; (1) Addul Makmur, more famous as datuk ri Bandang (2) Sulaiman, more famous as Datuk Patimang. (3) Abdul Jawad, who is better known as Datuk ri Tiro. The method of the Islamization process in Sulawesi was carried out using several approaches including: through the Palace, politics, customs, trade, and diplomacy or dialogue. The development of Islamic education in Sulawesi is classified into two, namely; non-formal education and formal education.